Headlines in history the 1200s - Siebold, Thomas (Headlines in history, 2001)
Divided into geographical areas, this book explores challenges civilizations faced in the 1200s, focusing on the Aztecs, the Arab-Islamic world, the Mongols, the Europeans, and the Chinese.